Tubular microscaffolds for studying collective cell migration - Xi, Wang; Sonam, Surabhi; Lim, Chwee Teck; Ladoux, Benoit (Academic Press Inc., 2018)
Epithelial cells demonstrate different collective migratory modes when encountering two (2D) and three dimensional (3D) microenvironment. While planar micropatterns and constraint have been shown to strongly impact collective cell migration (CCM), how out-of-plane curvature and 3D confinement will affect epithelial organization and dynamics remains largely unknown. This is likely due to lack of proper 3D microscaffolds for studying CCM. In this chapter, we briefly review the latest achievement in microengineering approaches to control 3D microenvironment of epithelial development. Then, we introduce convenient and simple methods of fabricating elastomeric tubular biocompatible microchannels as 3D cell culture scaffolds. Afterwards, we describe in detail the experimental set-up for observing 3D coordinated cell migration on curved surfaces and under spatial constraint. Finally, we provide an approach to analyze 3D dynamics using available techniques for 2D images.
CRIS-Team Scopus Importer:2024-02-19
Keywords: 3D cell culture; 3D image process; 3D imaging; Collective epithelial migration; Microtube; Tubular microchannel